Media2gether: Sharing Media during a Call - Forghani, Azadeh; Venolia, Gina; Inkpen, Kori (ACM Group 2014, 2014)
Telephone calls and videoconferencing are ubiquitous parts of everyday life. As the content of the call may extend beyond just words, people share applications and media using techniques such as screen sharing and email attachments. Little is known about the prevalence of this behavior and the benefits it can provide. We conducted a survey and a lab study to examine media sharing during a video call and found that it can be useful as well as emotionally engaging. Participants indicated that they would be more likely to have more frequent and longer calls if media sharing were easy. Overall, this work demonstrates the importance of exploring communication media that augment and enrich our everyday activities.